Making global learning universal : promoting inclusion and success for all students - Landorf, Hilary; Doscher, Stephanie; Hardrick, Jaffus (Stylus, copublished with NAFSA, 2018)
"The authors conceptualize global learning as the process of diverse people collaboratively analyzing and addressing complex problems that transcend borders of all kinds. They demonstrate how institutions can enable all students to determine relationships among diverse perspectives on problems and develop equitable, sustainable solutions for the world's interconnected human and natural communities. What's more, they describe how a leadership process--collective impact--can enable all stakeholders across departments and disciplines to align and integrate universal global learning throughout the institution and achieve the aims of inclusive excellence"--